Whatsapp to The Rescue: Automated Billing Reminders - Daffa Harastha Musyaffa; Ririn Ikana Desanti; Suryasari Suryasari (G-Tech: Jurnal Teknologi Terapan, 2024)
This research takes a case study approach to a company that provides digital marketing services. The company still relies on a manual process to record transactions on a spreadsheet. Their admin keeps track of clients' hosting and domain information in a Microsoft Excel file, and customers are not notified of their lease payment deadline in advance. There are also certain billing issues for service and subscription costs that are issued to customers. The proposed system is built utilizing the rapid application development (RAD) methodology. This method enables rapid system development. Furthermore, the RAD technique requires user participation during system development. The system was created using the PHP programming language, the CodeIgniter 3 framework, and MySQL as the database. It also utilizes the PHP WhatsApp Gateway API. The final outcome is a web-based billing tracking system that will send billing information to consumers via WhatsApp and email, as well as a notification of payment.